2011
DOI: 10.1089/end.2010.0624
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Intraoperative Fluoroscopy Utilization Reduces Radiation Exposure During Ureteroscopy

Abstract: Providing surgeons with feedback on their fluoroscopy usage reduces patient and surgeon radiation exposure. Implementing such a tracking system requires minimal changes to existing operating room staff workflow. Further study is warranted to study the impact of this program on other procedures that utilize fluoroscopy in urology and other specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“…Factors associated with reduced fluoroscopy time have been previously shown to be female sex and distal ureteral stone location, while factors associated with increased fluoroscopy time were the use of a ureteral sheath, ureteral balloon dilation, stent placement and presence of hydronephrosis [9].…”
Section: Discussionmentioning
confidence: 97%
“…Factors associated with reduced fluoroscopy time have been previously shown to be female sex and distal ureteral stone location, while factors associated with increased fluoroscopy time were the use of a ureteral sheath, ureteral balloon dilation, stent placement and presence of hydronephrosis [9].…”
Section: Discussionmentioning
confidence: 97%
“…Lower total exposure times have been found when there is routine documentation of fluoroscopy times in official reports (40%) or when feedback is provided (24%). 10, 23 In addition, specialized equipment such as laser-guided c-arms and a dedicated radiologic technologist familiar with the nuances of pediatric ureteroscopy may also be important components of an overall dose reduction program. 14 Finally, the introduction of new technologies may be able to reduce doses in the future as demonstrated by the success of pulsed fluoroscopy and digital imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found a 24% reduction in total fluoroscopy time when surgeons were provided feedback on usage and 40% lower times when radiologists specifically included total duration in their dictated reports. 22, 23 …”
Section: Discussionmentioning
confidence: 99%